Effectiveness of AADE7 Self-Care Behaviors on Improving Self-Efficacy in Type 2 Diabetes Patients: A Quasi-Experimental Controlled Study - Nurbani Nurbani; Winellia Winellia; Raju Kapadia (Poltekkes Kemenkes Bandung, 2026)
Background: Type 2 diabetes mellitus is a chronic disease that requires long-term self-management to prevent complications and improve quality of life. One of the key psychological factors influencing successful self-management is self-efficacy. Low self-efficacy may hinder patients’ adherence to recommended self-care behaviors. Health education based on the American Association of Diabetes Educators AADE7™ Self-Care Behaviors provides a comprehensive educational framework to enhance patients’ confidence and ability to manage their condition. Objective: This study aimed to analyze the effect of AADE7™-based health education on self-efficacy among patients with type 2 diabetes mellitus in Singkawang City. Methods: A quasi-experimental study with a pre–post test design and a control group was conducted. A total of 52 respondents were selected using purposive sampling, consisting of 26 participants in the intervention group and 26 in the control group, recruited from several community health centers in Singkawang City between April and August 2021. The intervention group received two sessions of AADE7™-based health education, while the control group received standard care without structured education. Self-efficacy was measured before and two weeks after the intervention. Statistical analysis was performed using the Wilcoxon Signed Rank Test and the Mann–Whitney U Test. Results: The results showed an increase in the mean self-efficacy score in the intervention group from 2.61 to 2.80, while the control group showed no significant change. Between-group analysis revealed a significant difference with a p-value of 0.02. Conclusion: AADE7™ Self-Care Behaviors-based health education is effective in improving self-efficacy among patients with type 2 diabetes mellitus